A new organisation for supplier involvement in vehicle design: the Italian automotive industry case. (1st January 2001) - Caputo, Mauro; Zirpoli, Francesco
This paper concerns the organisational solutions that best match the need to manage the new product development process in a context of the growing pace of new product introduction, high product variety and complexity, and strong supplier involvement in automotive component design. A very recent organisational structure for new product development at Fiat Auto, a global car manufacturer, will be presented and discussed in the light of recent literature. Strategies based on a major supplier involvement in design seem to benefit from the so-called extended platform organisation, and from the centralisation of component design responsibilities in a newly created organisational unit. This latter facilitates supplier involvement at the concept stage of development and, at the same time, allows the leverage of components and systems technology across models. This setting provides a valid counteraction against some pitfalls of the traditional platform based structure, in which the involvement of suppliers at the concept stage is often too idiosyncratic to the specific model under development, incurring diseconomies of scale and scope.